2008
DOI: 10.2478/v10045-008-0019-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Some Inert Diluents of Neem Kernel Powder on Protection of Sorghum Against Pink Stalk Borer (Sesemia Calamistis, Homps) in Nigerian Sudan Savanna

Abstract: Neem (Azadirachta indica) kernel powder (NKP) mixed 1:1 (weight basis) with some inert diluents (fine-sand, kaolin-dust, and saw-dust) were applied into the whorls of sorghum seedlings . Cost-benefit analysis shows that it was financially most beneficial to use NKP + fine-sand to control S. calamistis on sorghum in Nigerian Sudan savanna.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…A very important finding of this study is that the RD used affects S. zeamais in ways similar to commercial DE formulations. The death of insects caused by DEs could be attributed to dehydration provoked by the abrasiveness of the small particles of this inert dust and by adsorption of oils from the body of the insects (Fields and Korunic, 2000;Kavallieratos et al, 2006;Okrikata and Anaso, 2019), which breaks the layer of wax on the epicuticle, exacerbating the fatal loss of water as reported by Subramanyam and Roesli (2000), and Okrikata and Anaso (2008). Ibrahim et al (2012) observed that DE reduced the production of progenies by ovicidal and larvicidal activities, increasing adult mortality and, reducing oviposition.…”
Section: Resultsmentioning
confidence: 98%
“…A very important finding of this study is that the RD used affects S. zeamais in ways similar to commercial DE formulations. The death of insects caused by DEs could be attributed to dehydration provoked by the abrasiveness of the small particles of this inert dust and by adsorption of oils from the body of the insects (Fields and Korunic, 2000;Kavallieratos et al, 2006;Okrikata and Anaso, 2019), which breaks the layer of wax on the epicuticle, exacerbating the fatal loss of water as reported by Subramanyam and Roesli (2000), and Okrikata and Anaso (2008). Ibrahim et al (2012) observed that DE reduced the production of progenies by ovicidal and larvicidal activities, increasing adult mortality and, reducing oviposition.…”
Section: Resultsmentioning
confidence: 98%
“…Peduncle damage occurs during the advanced stage of the crop. Since application of treatments into the funnel of sorghum stops at the booting stage, it is obvious that the ability of the neem based treatments to suppress peduncle damage could be due to some level of persistence and systemic action (van den Berg and van Rensburg, 1991;Okrikata and Anaso, 2008). (Adane and Asmare, 2006;Chunshan et al, 2011) reported the very high efficacy of neem products in controlling stemborer infestations.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion and severity of leaves injured were computed from randomly selected leaves (10 leaves/plot) at 50% vegetative, 50% flowering, and 50% fruiting stages and pooled using the method described by Okrikata and Anaso (2008) and Okrikata et al (2020) wherein leaves were scaled 0 -4 for severity of injury: 0 (0% leaf injury), 1 (1 -25% leaf injury), 2 (26 -50% leaf injury), 3 (51 -75% leaf injury), 4 (76 -100% leaf injury). Scores obtained per plot were then converted to Attack severity (%) by the equation; Where: ∑ n = summation of individual injury scores/plot, N = number of scores taken/plot (= 10), and 4 = highest score on the scale.…”
Section: Assessment Of Leaf Injury and Growth Indicesmentioning
confidence: 99%